Shared Common Ancestry of Rodent Alphacoronaviruses Sampled Globally - Tsoleridis, Theocharis; Chappell, Joseph G.; Onianwa, Okechukwu; Marston, Denise A.; Fooks, Anthony R.; Monchatre-Leroy, Elodie; Umhang, Gérald; Müller, Marcel A.; Drexler, Jan F.; Drosten, Christian; Tarlinton, Rachael E.; McClure, Charles P.; et al. (Viruses, 2019)
The recent discovery of novel alphacoronaviruses (alpha-CoVs) in European and Asian rodents revealed that rodent coronaviruses (CoVs) sampled worldwide formed a discrete phylogenetic group within this genus. To determine the evolutionary history of rodent CoVs in more detail, particularly the relative frequencies of virus-host co-divergence and cross-species transmission, we recovered longer fragments of CoV genomes from previously discovered European rodent alpha-CoVs using a combination of PCR and high-throughput sequencing. Accordingly, the full genome sequence was retrieved from the UK rat coronavirus, along with partial genome sequences from the UK field vole and Poland-resident bank vole CoVs, and a short conserved ORF1b fragment from the French rabbit CoV. Genome and phylogenetic analysis showed that despite their diverse geographic origins, all rodent alpha-CoVs formed a single monophyletic group and shared similar features, such as the same gene constellations, a recombinant beta-CoV spike gene, and similar core transcriptional regulatory sequences (TRS). These data suggest that all rodent alpha CoVs sampled so far originate from a single common ancestor, and that there has likely been a long-term association between alpha CoVs and rodents. Despite this likely antiquity, the phylogenetic pattern of the alpha-CoVs was also suggestive of relatively frequent host-jumping among the different rodent species.